Concept of social security in Islam with special reference to zakat, waqaf and faraid - Mohamad Amin, Noor Shuhadawati; Ali Mohamed, Ashgar Ali (LexisNexis, 2016)
Social security has been regarded as one of the fundamental human rights. In Islam, social security originated from the concept of charity. This is evident from a number of verses in Al-Quran and Hadith emphasising on the importance of giving charity. Charity has been further developed into a more complex social security systems namely zakat, waqaf and faraid based on a few salient principles in Islam legalised by Al-Quran and Hadith. These social security systems which have been introduced during the time of the Prophet Muhammad pbuh are still implemented today particularly in Muslim states. Therefore, this paper aims to examine the current practice in Kuwait and Malaysia and to what extent the systems have been modified to suit the present needs of the Muslims community.